If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1 + -2y) + -5 = 6y + -2 (1 * 3 + -2y * 3) + -5 = 6y + -2 (3 + -6y) + -5 = 6y + -2 Reorder the terms: 3 + -5 + -6y = 6y + -2 Combine like terms: 3 + -5 = -2 -2 + -6y = 6y + -2 Reorder the terms: -2 + -6y = -2 + 6y Add '2' to each side of the equation. -2 + 2 + -6y = -2 + 2 + 6y Combine like terms: -2 + 2 = 0 0 + -6y = -2 + 2 + 6y -6y = -2 + 2 + 6y Combine like terms: -2 + 2 = 0 -6y = 0 + 6y -6y = 6y Solving -6y = 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -6y + -6y = 6y + -6y Combine like terms: -6y + -6y = -12y -12y = 6y + -6y Combine like terms: 6y + -6y = 0 -12y = 0 Divide each side by '-12'. y = 0 Simplifying y = 0
| 2a-10=44+8a | | -2d+18-4b=60 | | 9x+2+5x+4= | | 4x^2=488 | | (x-30)*.5=100 | | -6(1a-2b)-2(5b-4a)= | | -.25x+6=.5x+3 | | y-35=4.7 | | 7x+7+5x+6= | | 4(x+2)-3x+5=x+5 | | x^2+18x=-32 | | 10x+7+4x+7= | | x^2=-169 | | 6x^2+18x^2= | | -2x+30=7(x+3) | | (2x-1)+2(3x+7)=6x-3 | | 12(1/6-2/3x)-20/3(-3/4) | | 2.458+45+16.29= | | 3w+5w=48 | | 5*p=40 | | 0.24=0.42 | | 3x-5+2=8 | | -x-3y=-32x+3y=5 | | -24=5(u-8)-7u | | -32+2y=-6y | | 2s=34 | | 3w(w)-(w-5)(w-3)=2w(w)+1 | | f-16=-32 | | 18-3x=-15 | | 45x+9y=63 | | 0.18x+0.2(x-3)=0.01(4x-1) | | X+12y=-40 |